The Influence Of Discipline And Motivation On Employee Performance In The Office Of The Environmental Office Of West Jakarta City Administration - Asesanti, Desy Ade (Pascasarjana Universitas Pasundan, 2025)
This study aims to analyze the effect of work discipline and work motivation on employee performance at the Office of the Environmental Agency of West Jakarta Administrative City. This research adopts a descriptive quantitative approach with an analytical method that includes instrument testing, classical assumption testing, descriptive analysis, simple linear regression testing, multiple linear regression testing, and various other statistical tests. The research sample consists of 69 respondents, selected using a saturated sampling technique. The results indicate that work discipline (X1) has a positive and significant effect on employee performance, with a t-value of 8.169 > t-table 1.996008 and a significance value of 0.000 < 0.05. Similarly, work motivation (X2) also has a positive and significant effect, with a t-value of 7.481 > t-table 1.996008 and a significance value of 0.000 < 0.05. Simultaneously, both work discipline and motivation influence employee performance, as evidenced by an F-value of 59.148 > F-table 3.136.